2016
DOI: 10.2514/1.j054211
|View full text |Cite
|
Sign up to set email alerts
|

Global Stability Analysis of a Compressible Turbulent Flow Around a High-Lift Configuration

Abstract: The purpose of this work is to analyze a complex high lift configuration for which significant regions of separated flow are present. Current state of the art methods have some difficulty to predict the origin and the progression of this separated flow when increasing the angle of attack. The mechanisms responsible for the maximum lift limit on multielement wing configurations are not clear; this stability analysis could help to understand the physics behind the phenomenon and to find a relation between the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 22 publications
4
13
0
Order By: Relevance
“…It is elongated in the streamwise direction, with largest magnitude close to the separation point of the base flow and in the shear layer of the recirculation region. This is in good agreement with the mode identified by Iorio et al (2016) on an NACA0012 at very high Reynolds number, Re = 6.0 × 10 6 . Superimposed onto the base flow, it modifies the location of the separation point and the size of the recirculation region.…”
Section: High-frequency Vortex-shedding and Low-frequency Stall Modessupporting
confidence: 89%
See 3 more Smart Citations
“…It is elongated in the streamwise direction, with largest magnitude close to the separation point of the base flow and in the shear layer of the recirculation region. This is in good agreement with the mode identified by Iorio et al (2016) on an NACA0012 at very high Reynolds number, Re = 6.0 × 10 6 . Superimposed onto the base flow, it modifies the location of the separation point and the size of the recirculation region.…”
Section: High-frequency Vortex-shedding and Low-frequency Stall Modessupporting
confidence: 89%
“…The very low-frequency oscillation of the flow observed around stall ensures that this scale-decoupling is valid in the present case. Previously, Iorio et al (2016) observed by using a fully turbulent RANS model, that a low-frequency oscillation eigenmode was observed for the NACA0012 airfoil when the flow separates. We will show in the following that such a spatiotemporal structure is also observed for the OA209 aerofoil and that it may be linked to the low-frequency oscillation of the lift coefficient observed near stall (Zaman et al 1987).…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The analysis aims to identify which features can naturally appear in the flow and become dominant for some particular value of the parameters. Depending on the nature of the phenomenon, the analysis can be performed over a steady base flow solution [16][17][18], over an averaged mean flow [19][20][21], or using time-stepping or DMD techniques for the study of transient phenomena [22,23]. On this work, steady base flows were considered to characterize the stability behaviour of the system.…”
Section: Introductionmentioning
confidence: 99%